Implementasi Manajemen Berbasis Sekolah Dalam Upaya Meningkatkan Mutu Pembelajaran Pendidikan Agama Islam - Luthfiana, Rinda (Journal of Education and Culture, 2023)
School-based management (SBM) is an education management model that gives autonomy to schools to determine school policies in order to improve the quality, efficiency, and equity of education. MBS is expected to improve the quality of learning, including Islamic Religious Education (PAI) learning. This study aims to examine the implementation of MBS in an effort to improve the quality of Islamic Education learning. This research uses a qualitative research method with a case study approach. The research subject was SMKS Dr. Indra Adnan Indragiri College Tembilahan. The results showed that the implementation of MBS at SMKS Dr. Indra Adnan Indragiri College has been going well. This can be seen from the active participation of various parties, namely the principal, teachers, students, parents, and the community. This participation is manifested in various activities, such as school program preparation, learning implementation, and learning evaluation. The implementation of MBS at SMKS Dr. Indra Adnan Indragiri College has positively affected the quality of PAI learning. This can be seen from the increase in student learning outcomes, the increase in student learning motivation, and the increase in students' spiritual and social attitudes. Based on the results of the study, it can be concluded that the implementation of MBS can be one of the efforts to improve the quality of PAI learning.